Communicative Language Teaching (CLT) on ELT Students’ Reading Comprehension: A Pre-experimental Study: English - Annisa Kurnia Asri (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
Reading was often considered as a passive skill, while in fact, reading requires the learners to actively read and understand the text by relating to their former knowledge. This pre-experimental study aimed to measure how effective Communicative Language Teaching (CLT) on students’ reading comprehension of of ELT department. TOEFL Reading Comprehension test was used as the instrument to collect the data from the pre-test and post-test score. The resulted of the non-parametric test of Wilcoxon test showed that there was no improvement after the CLT approach was implemented (the p-value is higher than 0.05 indicating that there was no significant effect). Some factors might determine the effectiveness include the student’s readiness in understanding English, and the inappropriate approach to teach reading skill that requires more on accuracy rather than fluency.